Concept Paper on Decentralisation and Local Governance. Module 1: definitions and concepts. - Olsen, Hans Bjørn (Concept paper, 2007)
SDC has been implementing projects in support to decentralisation and local governance for about 15 years. Today, arounf 2/3 of SDC's country programmes include a support to local governance and/or decentralisation. For this reason, an independent evaluation of  SDC’s achievements on “Decentralisation  and local governance” took place in 2006‐2007. One of the recommendations of this evaluation  was to  carry out  a capitalisation of SDC’s experiences in this field. SDC’s  Governance  Division has been charged with implementing this recommendation and  has planned a two‐step process: first to clarify concepts; and secondly, to identify SDC’s practical lessons learnt in this field.  The present document has 3 main objectives: ‐To further a common understanding about concepts linked to decentralisation and local governance  within SDC (HQs and field). ‐ To give basic conceptual elements for capacity building activities in decentralisation ‐ The document does not pretend to be an academically precise paper, but rather a short and succinct  presentation of the various concepts. Therefore, this document does  not  present  a collection of practical experiences from SDCs many  interventions in developing countries, but is the 1st  module of a series of two documents. The 2nd  module  will be published  at the  end of 2008 and will include  practical and concrete recommendations and tips,  which will compiled at the capitalisation workshop of SDC’s experiences in supporting decentralisation  and local governance processes (planned for June 2008).
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; decentralization / descentralização; governance / governação

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde